1992
DOI: 10.1016/0378-1097(92)90356-s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of killer-resistant strains of Saccharomyces cerevisiae isolated from spontaneous fermentations

Abstract: A study of 26 killer-resistant wine strains of Saccharomyces cerevisiae, isolated during spontaneous fermentations in three vineyards in NW Spain, was carried out employing several methods that included a spheroplast-killing assay and analysis of chromosomal DNA patterns by pulse-field agarose electrophoresis. The results showed that 92% of the strains were derivatives of K2 killer toxin producing wine strains isolated from the same fermentations, and that they could be grouped into four different karyotypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…In this study it was observed that the killer response seems to be race-specific and that the best flor yeasts (S. cerevisiae (beticus) and S. cerevisiae (cheresiensis)) ( Table 5) are resistant to both K, and K, killer toxins (except B16, which was K, sensitive), although they are nonproducers (Table 6). In line with these results it has been reported that the inability to produce killer toxins by resistant strains is favoured by an increase in fermentative capacity (Cansado et al, 1992).…”
Section: Discussionsupporting
confidence: 67%
“…In this study it was observed that the killer response seems to be race-specific and that the best flor yeasts (S. cerevisiae (beticus) and S. cerevisiae (cheresiensis)) ( Table 5) are resistant to both K, and K, killer toxins (except B16, which was K, sensitive), although they are nonproducers (Table 6). In line with these results it has been reported that the inability to produce killer toxins by resistant strains is favoured by an increase in fermentative capacity (Cansado et al, 1992).…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly however, chromosome DNA pulsed field gel electrophoresis of 26 killerresistant N (neutral) wine strains of S. cerevisiae revealed that 92 % were derivatives of K2 killer toxin producing strains that had lost the ability to produce active toxin (16). Similar results were obtained in a Bordeaux winery (17) where it was observed that one karyotype of S. cerevisiae was stable and dominant in different wine vessels over a 2-year period.…”
Section: Among Yeastssupporting
confidence: 68%
“…Recently, interest in the development of bacteriocins as food preservatives (14) and in the use of the killer factors for industrial applications has increased (7,13,29,30). However, the role that killer activity may have as a mechanism of antagonism among yeasts in natural environments is not clear, and the conditions governing their behavior in various niches are mostly unknown.…”
mentioning
confidence: 99%
“…However, the role that killer activity may have as a mechanism of antagonism among yeasts in natural environments is not clear, and the conditions governing their behavior in various niches are mostly unknown. In spite of this lack of knowledge, the use of killer toxins to control yeast populations during fermentations has been postulated for beer and wine (7).…”
mentioning
confidence: 99%